The endogenous antioxidant ability of royal jelly in Drosophila is independent of Keap1/Nrf2 by activating oxidoreductase activity. - Wen, D.; Xie, J.; Yuan, Y.; Shen, L.; Yang, Y.; Chen, W. (Insect Science, 2024)
Royal jelly (RJ) is a biologically active substance secreted by the hypopharyngeal and mandibular glands of worker honeybees. It is widely claimed that RJ reduces oxidative stress. However, the antioxidant activity of RJ has mostly been determined by in vitro chemical detection methods or by external administration drugs that cause oxidative stress. Whether RJ can clear the endogenous production of reactive oxygen species (ROS) in cells remains largely unknown. Here, we systematically investigated the antioxidant properties of RJ using several endogenous oxidative stress models of Drosophila. We found that RJ enhanced sleep quality of aging Drosophila, which is decreased due to an increase of oxidative damage with age. RJ supplementation improved survival and suppressed ROS levels in gut cells of flies upon exposure to hydrogen peroxide or to the neurotoxic agent paraquat. Moreover, RJ supplementation moderated levels of ROS in endogenous gut cells and extended lifespan after exposure of flies to heat stress. Sleep deprivation leads to accumulation of ROS in the gut cells, and RJ attenuated the consequences of oxidative stress caused by sleep loss and prolonged lifespan. Mechanistically, RJ prevented cell oxidative damage caused by heat stress or sleep deprivation, with the antioxidant activity in vivo independent of Keap1/Nrf2 signaling. RJ supplementation activated oxidoreductase activity in the guts of flies, suggesting its ability to inhibit endogenous oxidative stress and maintain health, possibly in humans.